The dog as a sentinel species for environmental effects on human fertility. Issue 6 (May 2020) - Sumner, Rebecca Nicole; Harris, Imogen Thea; Van der Mescht, Morne; Byers, Andrew; England, Gary Crane William; Lea, Richard Graham
Abstract : Despite the vast body of evidence that environmental toxicants adversely affect reproductive development and function across species, demonstrating true cause and effect in the human remains a challenge. Human meta-analytical data, showing a temporal decline in male sperm quality, are paralleled by a single laboratory study showing a similar 26-year decline in the dog, which shares the same environment. These data are indicative of a common cause. Environmental chemicals (ECs) detected in reproductive tissues and fluids induce similar, short term, adverse effects on human and dog sperm. Both pre- and post-natal stages of early life development are sensitive to chemical exposures and such changes could potentially cause long term effects in the adult. The environmental 'pollutome' (mixtures of ECs) is determined by industrialisation, atmospheric deposition and bioaccumulation and characterises real-life exposure. In Arctic ecosystems, dietary and non-dietary chemical contaminants are detectable in biological tissues and linked with adverse health effects in both dogs and their handlers. In the female, such exposure could contribute to disorders such as ovarian insufficiency, dysregulated follicle development, ovarian cancer, and polycystic ovarian syndrome. In the dog, ovarian chemical concentrations are greater in the testis. In addition, preliminary studies indicate that dietary exposures may influence the sex ratio in the offspring in favour of females. Within this article, we review current knowledge on chemical effects on human reproduction and suggest that the dog, as a sentinel species for such effects, is an essential tool for addressing critical data gaps in this field.